Survey and Performance Evaluation of Jamgodrani Hills and Nagda Hill Wind Farm in Madhya Pradesh, India – A Case Study - kumar, Sachin; Pandey, Priyanka (Elsevier Ltd, 2014)
Today, most of the electricity generated comes from fossil fuels (coal, oil, and natural gas). These fossil fuels have finite reserves and will run out in the future. The negative effect of these fossil fuels is that they produce pollutant gases when they are burned in the process to generate electricity. Fossil fuels are a non-renewable energy source. However, renewable energy resources (solar, wind, hydro, biomass, geothermal and ocean) are constantly replaced, hence will not run out, and are usually less polluting. Due to an increase in greenhouse gas emissions more attention is being given to renewable energy. As wind is a renewable energy it is a clean and abundant resource that can produce electricity with virtually no pollutant gas emission. Induction generators are widely used for wind powered electric generation, especially in remote and isolated areas, because they do not need an external power supply to produce the excitation magnetic field. Furthermore, induction generators have more advantages such as cost, reduced maintenance, rugged and simple construction, brushless rotor (squirrel cage) and so on. This paper presents the detailed survey on performance of wind farms situated at Jamgodrani hills and Nagda hill, near Dewas city in Madhya Pradesh, India. Variation of various performance indices such as total yearly generation, total availability of grid, total availability of wind generator, total generating units per wind generator and capacity utilization factor is discussed for wind farm on Jamgodrani hills and Nagda hill respectively.Latter, it introduces a simple and direct formula based on complex impedance matrix method to calculate the minimum excitation capacitance (Cmin) and corresponding maximum frequency (fmax)required for successful voltage build up across the terminal of three phase dual winding induction generator when operating on 225kW rating, used as wind generator in wind farm and variation of minimum excitation capacitance as well as corresponding maximum frequency is also being plotted for various conditions of load and speed.
Keywords: Matlab/ Simulin; Renewable energy; Self-excited induction generator (SEIG); Total harmonic distortion (THD); Wind energy